Semantic interconnection in the prophetic speech - Housein, Usra K. (Al-Adab Journal, 2021)
How semantic correlation enables the listener to recognize the flow of meaning resulting from the organization of the text of the speech and cohesion, And has become a rhetorical text communication unit understandable homogeneous organization and sequence of construction and the link between sentences speech row.Shows the creativity of Prophet Mohammad in the selection and installation of the vocabulary within the context of the explosion of energies bearing in mind the meanings of the vibrant place to conditions, This communication between the holder and the message recipients of the speech is the foundation upon which to build in the face of social language, It is the relationships and events, which dominates the atmosphere hour performance of the article and determine the significance and the subject comes from a concerted attitudes and texts.Valkhtabh happened and my goal for the content and position of the contact, communication and the actual practice of social text operative achieves the intent and acceptance by informing and influencing perceived in a certain way information between the event and context of verbal, To understand the event rhetorical means knowing the sender, the receiver, and the relationship between them in which the temporal and spatial, Valkhtaib has a clear impact on the subject of rhetoric and content, construction and context, he is controlling element in the subject and content and the receiver upon the listener to follow Khatib in what he hears and understands what is meant by the sermon of indication and suggestion